Eliciting cues to deception by tactical disclosure of evidence: the first test of the Evidence Framing Matrix - Granhag, Pär Anders (Legal and criminological psychology, 2013)
Purpose. Research on real-life suspect interviews shows that disclosure of evidence is a very common tactic and that it occurs in all phases of the interview. It is therefore remarkable that there is hardly any research on the effectiveness of different disclosure tactics. The aim of this study was to examine the effects of three different disclosure tactics: presenting the evidence early and two versions of the Strategic Use of Evidence (SUE) technique. Methods. For the SUE-Basic technique (SUE-B), the evidence was disclosed late in the interview. For the SUE-Incremental technique (SUE-I), we used a stepwise disclosure tactic derived from the so-called Evidence Framing Matrix. The tactic consists of revealing evidence of increasing strength and precision. A mock-theft scenario was employed with 195 participants who were randomly allocated to one of six conditions: guilty or innocent suspects were interviewed with one of the three techniques. Two measures of inconsistency were used as dependent variables: statement-evidence inconsistency and the newly developed within-statement inconsistency. Results. By interviewing with SUE-I, strong cues to deception were elicited, especially for the statement-evidence inconsistency variable. For the SUE-B, significant but smaller differences between guilty and innocent suspects were obtained. Conclusions. We found that both when and how the evidence was disclosed moderated the effectiveness of disclosure. With respect to when, it was more effective to disclose the evidence late (vs. early), and with respect to how, it was more effective to disclose the evidence in a stepwise (vs. direct) manner. The tactical aspects of evidence disclosure are discussed.